Translation Analysis of Idiomatic Expression Found In “Zootopia” Movie - Syawal, Syawaliyah Putri Andini; Hilman, Evert Haryanto; Agustina, Maftuchah Dwi (Asosiasi dosen IDEBAHASA KEPRI, 2023)
This research used the data source